AKTIVITAS ANTIOKSIDAN EKSTRAK KASAR DAN EKSTRAK TERPURIFIKASI DAUN KELOR (Moringa oleifera) DENGAN METODE DPPH - Pertiwi, Krisna Kharisma; Imulda, Asih; Hesturini, Rosa J; Juliasari, Nindy Dwi (Jurnal Buana Farma, 2025)
Antioxidants play a crucial role in maintaining cellular integrity and preventing various biological damage processes that underlie the development of degenerative diseases. Moringa oleifera leaves are known to contain bioactive compounds with antioxidant activity; however, comparative data on the antioxidant potential of crude and purified extracts remain limited. This study aimed to compare the antioxidant activity of crude and purified Moringa oleifera leaf extracts using the DPPH method. Extraction was performed by maceration with 96% ethanol, followed by purification through liquid–liquid extraction using an ethanol–n-hexane mixture (1:1). Phytochemical screening was conducted on both extracts, and antioxidant activity was evaluated at concentrations of 20–100 ppm in triplicate. IC₅₀ values were determined using linear regression and statistically analyzed. The yields of the crude and purified extracts were 20.77% and 13.50%, respectively. Phytochemical analysis confirmed the presence of flavonoids, tannins, and saponins in both extracts. The purified extract exhibited stronger antioxidant activity (IC₅₀ = 68.040 ± 0.140 ppm) compared to the crude extract (IC₅₀ = 77.372 ± 0.312 ppm) (p < 0.05), although both were less potent than vitamin C as a positive control (IC₅₀ = 5.823 ± 0.128 ppm). These findings indicate that the purification process enhances the antioxidant potential of Moringa oleifera leaves by concentrating active components. This study provides scientific support for the potential use of purified Moringa leaf extract as an active ingredient in natural antioxidant supplements or cosmetic formulations.